Our families, our societies, and the new media between undermining and the prospects of the building - Shukri, Ahmad Khaled; Abdallah, Walid Hussein (Journal of Humanities & Social Sciences, 2021)
This research includes an illustration of the aimed meaning of the new media, its forms and features, and studying its impact on the Islamic families and societies. It has appeared that its impact can be divided into a positive side which presents by easy access to information, reducing time and effort, removing the obstructive barriers to gain knowledge and so. In addition to that, there is a negative side that has a huge and hazardous impact particularly on youth and all of the society members in general. Moreover, some of its impacts might be ruined for individuals, families, and societies, and this overwhelming torrent must be faced by wisdom, good behavior, guidance, and finding a capable alternative who can make a positive impact.
Keywords: new media; family and society; demolition and construction